Energy sustainability in operations: an optimization study. Issue 9 (October 2016) - Shibin, K.; Gunasekaran, Angappa; Papadopoulos, Thanos; Childe, Stephen; Dubey, Rameshwar; Singh, Tripti
Abstract In recent years, energy sustainability has attracted increasing attention from scholars, policy makers, and practitioners. However, in practical competitiveness, companies also have to maintain flexibility to deliver customer requirements. Existing theory has largely seen flexibility and sustainability as separate issues, ignoring their relationship. To address this gap, we attempt to explore energy sustainability using flexible operations management practices in India. Following a case research methodology, we investigate how flexible operations management practices embraced by a leading organization that minimizes energy consumption in plants with better resource utilization and better quality of work life for staff to meet the future requirements based on market forecast. We solve a real-time multi-criteria strategic capacity planning problem with multiple objectives such as throughput maximization, waste minimization, and resource utilization maximization by using discrete event simulation technique. Our data stems from ongoing research within a car manufacturing company in India, located at Pune. Shift timings, setup time, production batch size, and differential rated capacities of plants are considered as the variables in this study. However, optimal routing flexibility combined with volume flexibility helps to achieve significant reduction in energy consumption. Finally, we offer future research questions on flexible operations management practices.